Analysis of histological and immunological parameters of metastatic lymph nodes from colon cancer patients reveals that T-helper 1 type immune response is associated with improved overall survival. Issue 45 (November 2016) - Nizri, Eran; Greenman-Maaravi, Nofar; Bar-David, Shoshi; Ben-Yehuda, Amir; Weiner, Gilad; Lahat, Guy; Klausner, Joseph
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Lymph node (LN) involvement in colonic carcinoma (CC) is a grave prognostic sign and mandates the addition of adjuvant treatment. However, in light of the histological variability and outcomes observed, we hypothesized that patients with LN metastases (LNM) comprise different subgroups. We retrospectively analyzed the histological sections of 82 patients with CC and LNM. We studied various histological parameters (such as tumor grade, desmoplasia, and preservation of LN architecture) as well as the prevalence of specific peritumoral immune cells (CD8 +, CD20 +, T-bet +, and GATA-3 + ). We correlated the histological and immunological data to patient outcome. Tumor grade was a significant prognostic factor even in patients with LNM. So was the number of LN involved (N1/N2 stage). From the morphological parameters tested (LN extracapsular invasion, desmoplasia in LN, LN architecture preservation, and mode of metastases distribution), none was found to be significantly associated with overall survival (OS). The mean OS of CD8 + low patients was 66.6 ± 6.25 versus 71.4 ± 5.1 months for CD8 + high patients ( P  = 0.79). However, T-helper (Th) 1 immune response skewing (measured by Th1/Th2 ratio >1) was significantly associated with improved OS. For patients with low ratio, the median OS was 35.5 ± 5 versus 83.5 months for patients with high Th1/Th2 ratio ( P  = 0.001). The histological presentation of LNM does not entail specific prognostic information. However, the finding of Th1 immune response in LN signifies a protective immune response. Future studies should be carried to verify this marker and develop a strategy that augments this immune response during subsequent adjuvant treatment.